2012
DOI: 10.1074/jbc.m111.314229
|View full text |Cite
|
Sign up to set email alerts
|

Affixing N-terminal α-Helix to the Wall of the Voltage-dependent Anion Channel Does Not Prevent Its Voltage Gating

Abstract: Background: There is ongoing controversy concerning the location and mobility of the N-terminal ␣-helix in VDAC1 during voltage gating. Results: mVDAC1 with the N-terminal ␣-helix cross-linked to ␤-strand 11 forms typical voltage-gated channels. Conclusion:The N-terminal domain of VDAC1 does not move independently during voltage gating. Significance: This study dramatically alters the current view of voltage gating dynamic in VDAC1.The voltage-dependent anion channel (VDAC) governs the free exchange of ions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
99
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(103 citation statements)
references
References 47 publications
3
99
1
Order By: Relevance
“…There have now been a number of studies confirming that this conformation probably resides in the "open" state of the channel (11,12).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…There have now been a number of studies confirming that this conformation probably resides in the "open" state of the channel (11,12).…”
Section: Resultsmentioning
confidence: 95%
“…Numerous studies have established the functional importance of the N-terminal ␣-helix in regulating the flux of metabolites through the channel (9,10), and the observation that it is localized within the pore makes it ideally suited to regulate the passage of ions and metabolites through the pore. Based on molecular dynamics simulations and a series of cross-linking studies, the structure is believed to reside in the "open" conformation, facilitating the passage of ATP and other nucleotides (11,12).…”
mentioning
confidence: 99%
“…17,18 Recent studies focused on the role of the a-helix by fixing it covalently to the barrel wall. 18,19 Mertins et al 18 demonstrated that fixing the helix at two different positions either impaired voltage-induced closure of the channel or produced an asymmetric gating that depended on the direction of the electric field. In contrast, Teijido et al 19 found voltageinduced gating despite restricted helix mobility.…”
Section: Introductionmentioning
confidence: 99%
“…Electron microscopy and bilayer measurements suggest moderate to large structural changes during channel closure (5,9,20). Models for gating mechanisms include rearrangements of the N-terminal ␣-helix, barrel deformations, a combination of helix and barrel motions to varying extent, and translocation of a membrane-embedded voltage sensor out of the membrane (4,(21)(22)(23)(24)(25)(26)(27). Although NADH enhances the channel voltage dependence and reduces nucleotide permeability of the outer mitochondrial membrane, ATP itself has no effect on VDAC gating (16,28).…”
mentioning
confidence: 99%